PREPARATION OF ARYLSULFONE DERIVATIVE OF POLYSTYRENE WITH P-TOLUENE SULFONYL CHLORIDE - CANSIZ, A; COSKUN, M; OZDEMIR, E (Marcel Dekker Inc, 1991)
The arylsulfone derivative of polystyrene was prepared by p-toluene sulfonyl chloride in the presence of anhydrous aluminum chloride in methylene chloride at three different temperatures. The sulfonated polystyrenes were characterized by IR spectrophotometer, H-1-NMR spectrometer and sulfur analyzer. Activation energy of the sulfonation reaction was found to be 38,0 kj mol-1 and 36,5 kj mol-1 from the results of HCl and sulfur determinations, respectively. Solubility parameters and densities of some sulfonated polystyrenes were also determinated.
Keywords: Halogenated Polymers; Stability